The micronutrient zinc inhibits EAEC strain 042 adherence, biofilm formation, virulence gene expression, and epithelial cytokine responses benefiting the infected host - Medeiros, Pedro (Landes Bioscience, 2013)
Enteroaggregative Escherichia coli (EAEC) is a major pathogen worldwide, associated with diarrheal disease in both children and adults, suggesting the need for new preventive and therapeutic treatments. We investigated the role of the micronutrient zinc in the pathogenesis of an E. coli strain associated with human disease. A variety of bacterial characteristics—growth in vitro, biofilm formation, adherence to IEC-6 epithelial cells, gene expression of putative EAEC virulence factors as well as EAEC-induced cytokine expression by HCT-8 cells—were quantified. At concentrations (≤ 0.05 mM) that did not alter EAEC growth (strain 042) but that are physiologic in serum, zinc markedly decreased the organism’s ability to form biofilm (P < 0.001), adhere to IEC-6 epithelial cells (P < 0.01), and express putative EAEC virulence factors (aggR, aap, aatA, virK) (P < 0.03). After exposure of the organism to zinc, the effect on virulence factor generation was prolonged (>3 h). Further, EAEC-induced IL-8 mRNA and protein secretion by HCT-8 epithelial cells were significantly reduced by 0.05 mM zinc (P < 0.03). Using an in vivo murine model of diet-induced zinc-deficiency, oral zinc supplementation (0.4 µg/mouse daily) administered after EAEC challenge (10(10) CFU/mouse) significantly abrogated growth shortfalls (by >90%; P < 0.01); furthermore, stool shedding was reduced (days 9–11) but tissue burden of organisms in the intestine was unchanged. These findings suggest several potential mechanisms whereby physiological levels of zinc alter pathogenetic events in the bacterium (reducing biofilm formation, adherence to epithelium, virulence factor expression) as well as the bacterium’s effect on the epithelium (cytokine response to exposure to EAEC) to alter EAEC pathogenesis in vitro and in vivo. These effects may help explain and extend the benefits of zinc in childhood diarrhea and malnutrition.